Meritocracy - Moreno del Río , Carmelo (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Desert is an increasingly valued attribute, in such a way that meritocracy has become a strong valid political device to order resources, incentives and social positions. At the same time, meritocratic logic challenges the idea of a fair democracy, based on non-discriminatory equality towards different people. It is worth asking if meritocracy and democracy can be complementary powers or, on the contrary, obey incompatible logics. The objective of this paper is to analyze the relationship between desert and an idea of just democracy. For doing so, this text is organized in several parts. The first one analyzes what desert consists in, based on the work of David Miller. The second part analyzes the arguments of three types of theoretical authors –liberals, communitarians and democratic egalitarians– who have debated this issue. The text concludes with some reflections on how it would be possible to facilitate that meritocracy can be subordinated to democratic values.